2022
DOI: 10.1186/s13741-022-00238-3
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative decrease of albumin (ΔAlb) as early predictor of complications after gastrointestinal surgery: a systematic review

Abstract: Background Postoperative complications are frequent after gastrointestinal surgery and early prediction remains an unmet need. Serum albumin shows a rapid decrease after surgery, and this decline (ΔAlb) may reflect the intensity of the surgical stress response and thereby be a predictor of postoperative complications. This study aimed to comprehensively review the available data on ΔAlb in gastrointestinal surgery. Methods PRISMA guidelines were fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…34,35 However, studies evaluating the association between intraoperative/postoperative hypoalbuminemia and PPC are limited. 36 In this study, we reported that low albumin levels (<3.0 g/dL) at the end of surgery were significantly associated with PPC risk. Patients referred for liver transplantation already suffered from hypoalbuminemia because of the decreased hepatic synthesis, rapid degradation because of structural change, 37 dilution effect from increased plasma volume, 38 and sequestration of circulating albumin in extracellular space.…”
Section: Discussionmentioning
confidence: 66%
“…34,35 However, studies evaluating the association between intraoperative/postoperative hypoalbuminemia and PPC are limited. 36 In this study, we reported that low albumin levels (<3.0 g/dL) at the end of surgery were significantly associated with PPC risk. Patients referred for liver transplantation already suffered from hypoalbuminemia because of the decreased hepatic synthesis, rapid degradation because of structural change, 37 dilution effect from increased plasma volume, 38 and sequestration of circulating albumin in extracellular space.…”
Section: Discussionmentioning
confidence: 66%
“…Postoperative hypoalbuminemia is frequently observed in patients undergoing major abdominal surgery [ 14 ]. Particularly, regarding serum albumin levels as an important indicator of perioperative hepatic function in patients undergoing liver transplantation, many studies have focused on whether perioperative hypoalbuminemia is associated with worse outcomes or whether albumin supplementation could improve postoperative outcomes, such as organ failure and survival [ 10 , 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Albumin is the most abundant protein in the extracellular matrix synthesized in liver tissue. Decreased albumin level is associated with malnutrition and cancer progression (14)(15)(16). Recently, serum albumin was reported to play an important role in systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%